EFEITOS DE NANOPARTÍCULAS COMERCIAIS DE ÓXIDO DE FERRO (Fe2O3): CITOTOXICIDADE, GENOTOXICIDADE E ESTRESSE OXIDATIVO - Batista-gallep, Tatiane Balbo; Pasquoto-stigliani, Tatiane; Guilger, Mariana; Rheder, Diogo Torres; Germano-costa, Tais; Bilesky-josé, Natalia; Fraceto, Leonardo Fernandes; Carvalho, Cleoni Dos Santos; Lima, Renata De (Sociedade Brasileira de Química, 2018)
This study presents the toxicological effects of iron nanoparticles (NP Fe2O3) using in vitro and in vivo tests. Initially nanoparticles were characterized physic-chemically followed by evaluation of cell viability using different cell lines. Allium cepa test and comet assay (cell lines and Danio rerio) were used for evaluation of genotoxicity. Oxidative stress analyses were performed using D. rerio exposed to NP-Fe2O3, and the enzymatic activity of the enzymes catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST) were evaluated. The results showed that initially nanoparticles had 65.55 nm, 0.24 of polydispersity of and 11.4 mV of zeta potential. Regarding cell viability, it was observed that this did not reach the IC50 up to the concentration 1 x 1010 NP mL-1. The in vitro comet assay showed that in concentrations 1.96 x108 and 109 NPs mL-1 these presented toxicity, for Allium cepa evaluation in concentrations 19.6 and 39.0 x109 NPs mL-1 presented significant damages when compared to the control. Oxidative stress showed that the liver was the most affected organ when compared to the control. Although studies show that iron nanoparticles do not lead to changes, further studies are needed to make sure they do not lead to environmental changes.
EFFECTS OF COMMERCIAL NANOPARTICLES OF IRON OXIDE (Fe2O3): CYTOTOXICITY, GENOTOXICITY AND OXIDATIVE STRESS
Keywords: iron oxide nanoparticles; zebrafish; viability; in vitro analysis; in vivo analysis